Economic benefit in repeat breeder cows using intrauterine infusion of penicillin and estrus synchronization followed by timed artificial insemination - Khair, Abul; Asaduzzaman, Md.; Sultana, Zinat; Talukder, Anup Kumar; Das, Ziban Chandra; Alam, Md. Golam Shahi; Shamsuddin, Mohammed (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Until recently, management of repeat breeding in cattle remains a major problem to dairy farmers. This study was carried out to improve the fertility in cows, those did not conceive after three or more consecutive services. Materials and methods: Twenty-three repeat breeding cows were selected from the Central Cattle Breeding Station and Dairy Farm (CCBS & DF), Savar, Dhaka, Bangladesh. Data of another 23 repeat breeding cows that conceived after four or more services were collected from the same farm as controls. The repeat breeders were synchronized for estrus with two injections of PGF2α 11 days apart and timed AI (TAI) was performed. Results: Seventeen of 23 cows had uterine infections. Intrauterine infusion of penicillin daily for three successive days from the following day of the first PGF2α injection resulted in 94.1% (16/17) recovery. Of 23 treated cows, four with estrus synchronization and TAI, and one with only AI after hormone treatment were detected pregnant by per rectal examination of the genital tract. By this pregnancy, the treated cows have advanced average of 131.6 days calving interval and days open, and thereby saved neat US 3,045.3 in comparison to control cows. Control group cows incurred losses of US 15,134.0 compared with average days open of the treated pregnant cows. Conclusion: Intrauterine infusion of penicillin can successfully recover the uterine infections, and estrus synchronization followed by TAI resulted in pregnancy in a proportion of repeat breeder cows with economic benefit that had a uterine infection. http://doi.org/10.5455/javar.2018.e298